EVALUATION OF SENSORY AND MICROBIOLOGICAL ANALOGUE MEAT MADE OF CASHEW FRUIT AND RED BEAN FLOUR - Ika Dyah Kumalasari; Gresa Dania Arta Dinata; Ibdal Satar (BPFP Faperta UNIB, 2022)
Cashew fruit contains high levels of vitamin C and has a high antioxidant content. This study aims to determine the acceptance of analog meat, the number of bacteria, and to determine the shelf life of analog meat made from cashew fruit (Anacardium occidentale L.) and red bean flour (Phaseolus vulgaris L.). The experiment used in this study was a single factor Completely Randomized (CRD) with 5 treatment levels %w/w design of cashew nuts and red bean flour, namely F1 (60%:20%); F2 (50%:30%); F3 (40%:40%); F4 (30%:50%); and F5 (20%:60%) with the addition of 20% white oyster mushroom for each formulation. The method used in this research is a sensory test, total plate number test, and observation of shelf life, then the data obtained will be analyzed by one way ANOVA test and further tests are carried out using Duncan to determine the significant difference between each treatment. The results showed that the sensory properties of the color parameter which had the highest value were F4 which had a significant effect on an average of 3.77, the aroma parameter which had the highest value was F3 which had a significant effect on an average of 3.80, the taste parameter which had the highest value was F1. significant effect on an average of 3.70, the texture parameter which has the highest value is F3 which has a significant effect on an average of 3.83, and the overall preference level parameter which has the highest value is F3 which has a significant effect on an average of 3.6. Be based 2019 BPOM regulations (ISO 4833-1; SNI 2897), the analogue meat of red bean flour F1, F2, F3, F4, and F5 has met the SNI 2897 standard requirements for analoge meat, and does not exceed the microbial contamination threshold with a vulnerability of 3.0 x 103 cfu/gto 18, 3 x 103 cfu/g. The shelflife prediction was 3-7days at room temperature, in which the analog meat has experienced changes in smell and appearance, however there was no change in smell and appearance upon stored at cold temperature for 1 -7 days.